2013
DOI: 10.1111/resp.12095
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of combined bronchoscopy and endobronchial ultrasonography, under LungPoint guidance for small peripheral pulmonary lesions

Abstract: The combination of EBUS-GS and LungPoint was useful for diagnosing small PPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 23 publications
8
76
1
Order By: Relevance
“…The probe position was an important factor in predicting the diagnostic yield of EBUS-GS-guided TBB. Previous reports have indicated the probe position to be the only significant diagnostic factor (7,8). In the multivariate analysis of the present study, the "within" PPL probe position was found to be significantly associated with a successful diagnosis using radial EBUS (OR=2.542; p=0.007).…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…The probe position was an important factor in predicting the diagnostic yield of EBUS-GS-guided TBB. Previous reports have indicated the probe position to be the only significant diagnostic factor (7,8). In the multivariate analysis of the present study, the "within" PPL probe position was found to be significantly associated with a successful diagnosis using radial EBUS (OR=2.542; p=0.007).…”
Section: Discussionsupporting
confidence: 47%
“…The diagnostic yield of EBUS-GS-guided TBB in small (! 30 mm) PPL has been reported to be 63-79% (4)(5)(6)(7)(8). The factors which affect the EBUS-GS diagnostic yield in PPL have been reported; however, some reports have indicated that the probe position is the only independent predictor of the EBUS-guided TBB diagnostic yield (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies (5,7,(14)(15)(16) also suggested that bronchus sign or the probe located in the center of the lesion were positive factors for a higher diagnostic yields of EBUS-GS. Besides, the application of virtual bronchoscope and electromagnetic navigation bronchoscope could assist the probe to reach the target lesion and improve diagnostic accuracy (23)(24)(25). The complication rate of EBUS-GS was 2%, which was not significantly lower than CT-TTNA (13%) in this study.…”
Section: Discussionmentioning
confidence: 58%